2018
DOI: 10.1097/md.0000000000012100
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative oral thyroid hormones to prevent euthyroid sick syndrome and attenuate myocardial ischemia-reperfusion injury after cardiac surgery with cardiopulmonary bypass in children

Abstract: Background:Both euthyroid sick syndrome and myocardial ischemia-reperfusion injury are common and have been significantly associated with morbidity and mortality after pediatric cardiac surgery with cardiopulmonary bypass. This single-center, prospective, double-blind, randomized placebo-controlled clinical pilot trial was designed to assess if preoperative oral thyroid hormone therapy could prevent the occurrence of euthyroid sick syndrome (ESS) and attenuate myocardial ischemia-reperfusion injury (IRI) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Thyroid hormones have important effects on the cardiovascular system, such as increasing cardiac output and decreasing systemic vascular resistance, which are predictive of good outcomes 24,25 . However, several studies have veri ed that cardiac surgery with CPB induces a marked depression of thyroid hormones 14,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones have important effects on the cardiovascular system, such as increasing cardiac output and decreasing systemic vascular resistance, which are predictive of good outcomes 24,25 . However, several studies have veri ed that cardiac surgery with CPB induces a marked depression of thyroid hormones 14,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Marwali et al and the Triiodothyronine supplementation in infants and children undergoing CPB (TRICC) trial found that T3 administration provides clinical advantages and reduces time to extubation (TTE) in patients younger than 5 months undergoing congenital heart disease surgery and no advantage for those older than 5 months. 29,31 The study of Zhang et al 42 found that thyroid hormone significantly decreased the requirement of inotropic drugs in the ICU and provided protection against myocardial IR injury in paediatric patients undergoing simple cardiac surgery with CPB. The study of Talwar et al 40 showed that oral T4 improved the cardiac index, reduced inotropic requirements, the duration of mechanical ventilation, ICU stay, and TISS in infants after surgery for complex congenital heart defects.…”
Section: Thyroid Hormones and Implications In Extracorporeal Circulatmentioning
confidence: 99%
“…In isolated dogs hearts, a bolus of T3 (0.2 µg/kg) after reperfusion increased coronary blood flow by decreasing coronary arterial resistance (123). The results of a double-blind, randomized placebo-controlled clinical trial suggested that 0.4 mg/kg taken orally once a day for 4 days before surgery may provide protection against myocardial IRI during cardiac surgery in children by increasing HSP70 and MHC-α expression, inducing pharmacological ischemic preconditioning (128). A study in humans that aimed to evaluate the effects of TH replacement therapy on systolic and diastolic function in SCH patients showed a statistically significantly increase in ejection fraction after five months of levothyroxine therapy (129).…”
Section: Thyroid Hormones: a Future Therapeutic Option?mentioning
confidence: 99%